Rapid Determination of Acarbose in Tablets by 1H NMR Spectroscopy - Wang, Cong; Zhang, Xiuli; Yu, Mingming (Current Pharmaceutical Analysis, 2020)
Introduction: Acarbose, an anti-diabetic drug, is commonly used to treat diabetes mellitus type 2. Determinationof acarbose is crucial for routine quality control of acarbose tablets. Materials and Methods: In this report, a rapid, stable and precise method was developed and validated for the quantification of acarbose in tablets by 1H NMR. Two characteristic signals at 5.80 and 2.31 ppm were used to determine acarbose. The assay was linear over a concentration range of 0.25-10.0 mg/mL. The precision was 0.26% and 1.02% for signals at 5.80 and 2.31 ppm, respectively. The average recoveries of acarbose were 99.7% and 99.2%, with RSD values 0.51% and 0.61% at two signals, respectively. Results and Discussion: The content of tested tablets was 100.4% and 100.8% of the label claim with RSD values 0.96% and 1.47% at two signals, which met the requirement of Chinese Pharmacopoeia criteria for content uniformity of tablets. The assay has been successfully applied to determine the content of acarbose in tablets for quality evaluation. Conclusion: This method has been successfully applied to determine the content of acarbose in tablets for quality evaluation.
Keywords: type 2 diabetes